Pengaruh Pemanfaatan Teknologi Informasi terhadap Produktivitas Karyawan di Sekretariat Daerah Provinsi Kalimantan Timur - Nia Novita Ramadhani; Jubaidi Jubaidi; Rinda Sandayani Karhab (Jurnal Ilmiah Manajemen dan Kewirausahaan, 2025)
This study aims to analyze the effect of the use of artificial intelligence (AI)-based technology on employee productivity at the Regional Information Secretariat of East Kalimantan Province. The research method used is a quantitative approach with data collection techniques through distributing questionnaires to 239 respondents selected from a total population of 593 employees. The data obtained was analyzed using simple linear regression to measure the extent to which AI utilization affects improvement. The results showed that there is a positive and significant influence between the utilization of AI-based information technology and employee productivity. This is evidenced by the p-value which is smaller than 0.05 and the regression coefficient which is positive. Thus, it can be concluded that the utilization of AI-based applications, such as document automation systems, data analysis tools, and intelligent communication media, contributes to improving the efficiency and effectiveness of employee work within the Regional Secretariat of East Kalimantan Province.